The intracranial system: A new interpretation of the Monro-Kellie doctrine - Anile Carmelo; Ficola Antonio; Santini Pietro (Archives of Anatomy and Physiology - Peertechz Publications, 2021)
In this paper we have reported our experience in several years in whom we have studied the phenomena correlated with the intracranial pressure. We have started to study different types of animals during an experimental condition of intracranial hypertension; we have observed many different configurations in spontaneous pathologic  humans, and, eventually, in last years we have passed to confirm our ideas modelling an intracranial system in a physical phantom made by a centrifugal pump, stainless steel for base, glass for the wall, elastic tube for the cerebrovascular tree and collapsible tubes for venous drainage. We have noted that there is some confusion about the so-called Monro-Kellie doctrine; the major part of the scientist believe in a sort of static interpretation given by the sum of the compartment which constitute the intracranial system (parenchyma, blood and cerebrospinal fluid). But we believe in a dynamic interpretation in which there is a constant balance between the arterial inflow and venous outflow during each cardiac cycle. In this paper we have focused on the results, obtained in the different preparations, animals, humans and in vitro, all confirming the assumption that there is no difference between arterial inflow and venous outflow.